# Difference between revisions of "Nabla derivative at left-scattered"

From timescalewiki

(Created page with "==Theorem== If $f$ is continuous at $t$ and $t$ is left-scattered, then $$f^{\nabla}(t) = \dfrac{f(t)-f(\rho(t))}{\nu(t)}.$$ ==Proof== ==References== ...") |
|||

Line 1: | Line 1: | ||

==Theorem== | ==Theorem== | ||

− | If $f$ is continuous at $t$ and $t$ is [[scattered point|left-scattered]], then | + | If $f$ is [[continuity|continuous]] at $t$ and $t$ is [[scattered point|left-scattered]], then |

− | $$f^{\nabla}(t) = \dfrac{f(t)-f(\rho(t))}{\nu(t)} | + | $$f^{\nabla}(t) = \dfrac{f(t)-f(\rho(t))}{\nu(t)},$$ |

+ | where $f^{\nabla}$ denotes the [[nabla derivative]], $\rho$ denotes the [[backward jump]], and $\nu$ denotes the [[backward graininess]]. | ||

==Proof== | ==Proof== |

## Latest revision as of 00:58, 23 August 2016

## Theorem

If $f$ is continuous at $t$ and $t$ is left-scattered, then $$f^{\nabla}(t) = \dfrac{f(t)-f(\rho(t))}{\nu(t)},$$ where $f^{\nabla}$ denotes the nabla derivative, $\rho$ denotes the backward jump, and $\nu$ denotes the backward graininess.